Clinical and Magnetic Resonance Imaging Results of Arthroscopic Repair of Intratendinous Partial-thickness Rotator Cuff Tears - Xiao, Jian (Chin Med J (Engl), 2015)
BACKGROUND: Partial-thickness rotator cuff tears (PTRCTs) are being diagnosed more often because of high-resolution magnetic resonance imaging (MRI). Compared with articular and bursal side tears, there have been few studies about evaluating the clinical and structural outcomes after intratendinous tear repair. METHODS: From 2008 to 2012, 33 consecutive patients with intratendinous PTRCTs underwent arthroscopic repair. All of them were retrospectively evaluated. The University of California at Los Angeles (UCLA) and constant scores were evaluated before operation and at the final follow-up. Postoperative cuff integrity was determined using MRI according to Sugaya's classification. RESULTS: At the 2-year follow-up, the average UCLA score increased from 16.7 ± 1.9 to 32.5 ± 3.5, and the constant score increased from 66.2 ± 10.5 to 92.4 ± 6.9 (P < 0.001). Twenty seven patients received follow-up MRI examinations at an average of 15.2 months after surgery. Of these 27 patients, 22 (81.5%) had a healed tendon, and five patients had partial tears. There was no association between functional and anatomic results. CONCLUSIONS: For intratendinous PTRCT, clinical outcomes and tendon healing showed good results at a minimum 2-year after arthroscopic repair.